Thin-body effects in double-gate tunnel field-effect transistors - Nguyễn, Đăng Chiến (IOP Publishing, 2024)
Scaling down the body thickness (Tb) of double-gate tunnel field-effect transistors (DG-TFETs) is helpful in suppressing short-channel effects (SCEs), but it may give rise to thin-body effects (TBEs). Based on 2-D device simulations, this study examines the mechanisms and influences of TBEs in DG-TFETs as Tb is scaled down. Differently from previous beliefs, the on-current degradation in thin-body DG-TFETs is not mainly caused by the volume effect, but rather by a newly defined TBE named lateralization effect. This is because the lateralization of tunneling direction significantly increases tunnel width, whereas the reduction of tunneling volume is quite limited due to narrow tunneling regions. To study the Tb-dependence of current, therefore, the vertical tunneling has to be taken into consideration. When considered as a TBE, the fringing field effect caused by reduction in Tb is not significant in degrading the on-current of thin-body DG-TFETs because the narrow tunneling regions are strongly gate-controlled. The only TBE that enhances the on-current is the coupling effect, but its role is only significant for low-bandgap bodies in which the coupling effect can efficiently promote the tunneling towards the body center. Not as previously thought that the quantum confinement effect (QCE) monotonically increased, it even decreases as Tb decreases down to sub-10 nm before turning to increase, thanks to the space sharing between proximate local quantum wells. A comprehensive understanding of the TBEs is useful for providing design insight, especially for determining the optimal Tb to maximize the on-current.